MODEL BANTUAN KEWIRAUSAHAAN BERBASIS PENGEMBANGAN SDM SEBAGAI UPAYA MEWUJUDKAN KEMANDIRIAN EKONOMI MUSTAHIK - Sholikha, Marhatus (Fakultas Ekonomi, UIN Maliki Malang, 2018)
Abstract: Human resources has important role to establish organization goals, in addition to accelerate realization of achievment goals, so it is needed a human resources development program as strategic step to fulfill needs of required abilities. This program is unlimited implementation by profit oriented organization, but included phylanthropy organization. This research use descriptive qualitative. The object of research is Rumah Zakat branch Malang, but it is focused on â€œMustahikâ€. The Data analysis technique use Analysis of data presentation method, data reduction, data display, conclusion and verification.Â The result show that the implementation of development program is one of many ways to form the independence of Mustahik in the global era which require competitive supremacy like teoritic abilities, conceptual, moral and technical skills. The organization provide competent presentator on his expertise and more specifically in enterpreunership and this is necessary to deliver motivation for founder member. After all the implementation of enterpreunership assistance based on human resources development being good assumed and optimum is measured by knowledge, hard skill, soft skill, sharia competence and mainly watched on independence (financial, spiritual and social) mustahik since following this program although the output who is generated still slightter than expected.Â